Comparative study of 3.4 micron band features from carbon dust analogues obtained in pulsed plasmas. Issue Volume 15:Issue S350(2019) (April 2019) - Cristina Gerber, Ioana; Chiper, Alina; Pohoata, Valentin; Mihaila, Ilarion; Topala, Ionut
Abstract: Syntheses of carbon dust analogues are key experiments in laboratory astrophysics, as an approach to study some chemical and topological features of interplanetary and interstellar carbon dust. We report a comparative experimental study for carbon dust analogues obtained in (1) an atmospheric pressure dielectric barrier discharge (DBD), fed with helium – saturated hydrocarbons gas mixtures, (2) a low pressure radio frequency (RF) discharge and (3) a pulsed laser deposition (PLD) experiment with a Nd:YAG laser and a graphite target. The aliphatic –C–H stretching band, known as the 3.4 micron feature, as well as the CH2 /CH3 ratio, the H/C ratio value and the physical appearance at microscopic scale, show a variability that is influenced by the synthesis method and the experimental parameters of each specific technique.